Phytochemical Screening of Purple Leaf Twig Extract - Alfiyandhini, Elya Nanda; Sunarwidhi, Anggit Listyacahyani; Octora, Metta; Mukhlisah, Neneng Rachmalia Izzatul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Purple leaf (Graptophyllum pictum L. Griff) is a plant that has antibacterial, antioxidant, anti-inflammatory and antidiarrheal benefits. Flavonoids, alkaloids, steroids, saponins, and tannins are some of the secondary metabolites found in the leaves that have antibacterial properties. This study aims to determine the content of phytochemical compounds in purple leaf twig extract. The method used is phytochemical screening to identify flavonoid, alkaloid, saponin, tannin, steroid and terpenoid compounds. The results of phytochemical screening showed that the purple leaf twig extract contained flavonoid, saponin and terpenoid compounds. However, it did not show any steroid compounds. The conclusion is that the identification of secondary metabolite compounds in purple leaf twig extract contains flavonoid, saponin and terpenoid compounds. In contrast to the content of secondary metabolite compounds in G. pictum twigs is different from that in its leaves.